An Economic Model of Machine Translation (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
With the advent of free, online translation services such as Google Translate, many people are now able to obtain information relatively effortlessly from a wide variety of foreign language sources. The translations from these services are often worse than those provided by professional, human translators, however, and the tradeoff between these two alternatives is not always clear. When should a professional be used, and when is machine translation sufficient? In this study, we discuss factors involved in the decision and illustrate their use with a predictive model.